The Influence of Work Environment and Workload on Employee Performance at PT Adis Dimension Footwear in Tangerang Regency - Muhammad, Ismail; Fahmi, Khairul (UJoST- Universal Journal of Science and Technology, 2025)
This study aims to determine the effect of work environment and workload on employee performance at PT Adis Dimension Footwear. This type of research is quantitative with an associative approach. The sample used was 30 respondents. Data analysis techniques used include multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the analysis show that the work environment (X1) has a positive and significant effect on employee performance (Y), with a regression coefficient value of 0.663 and a calculated t value of 4.740 (significance 0.000 <0.05). Conversely, workload (X2) has a negative and significant effect on employee performance, with a regression coefficient value of -0.218 and a calculated t value of -2.115 (significance 0.044 <0.05). The F-test shows that simultaneously the work environment and workload have a significant effect on employee performance, with a calculated F value of 11.358 and a significance of 0.000. The coefficient of determination (R²) of 0.457 indicates that 45.7% of the variation in employee performance can be explained by these two independent variables, while the remaining 54.3% can be influenced by other variables such as compensation and indications of low employee commitment. Thus, it can be concluded that the work environment and workload, both partially and simultaneously, have a significant effect on employee performance at PT Adis Dimension Footwear.